Distress and eustress: an analysis of the stress experiences of offshore international students - Gong, Wuwei; Geertshuis, Susan A. (Frontiers in Psychology, 2023)
Introduction The popularity of online learning provides higher education institutions with opportunities to deliver remote educational programs for international students who remain in their home countries but enroll in overseas universities. Yet the voices of offshore international students (OISs) have been rarely heard. This study focuses on the stress experiences of OISs, aiming to investigate the perception of stressors, specific responses, and stress management strategies pertaining to distress (negative stress) and eustress (positive stress). Methods Semi-structured interviews were conducted in two phases with 18 Chinese postgraduate OISs enrolled in a range of institutions and disciplines. Interviews took place online and were analyzed thematically to explore participants’ experiences. Results Stress was found to originate from both socially- and task-based factors, closely related to participants’ need to integrate into their on-campus community and gain useful knowledge and skills. Particular sources of stress were associated with distinct perceptions and subsequent responses and management strategies. Discussion A summarizing theoretical model is offered to highlight the separate construct of distress and eustress, indicating tentative causal relationships to extend existing stress models to an educational context and provide new insights into OISs. Practical implications are identified and recommendations are provided for policy-makers, teachers, and students.